2017
DOI: 10.1111/iju.13516
|View full text |Cite
|
Sign up to set email alerts
|

Perilla extract improves frequent urination in spontaneously hypertensive rats with enhancement of the urothelial presence and anti‐inflammatory effects

Abstract: The present findings suggest that perilla extract improves frequent urination, and this improvement seems to be mediated, at least in part, by enhancement of the urothelial presence and by the anti-inflammatory effects of perilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Several studies have reported an association between urothelial barrier dysfunction and inflammation-related LUTD. Spontaneously hypertensive rats (SHRs), which is a rat model of OAB, showed bladder inflammation and impaired urothelial barrier function with a decreased number of UPs [ 18 ]. In the SHRs, supporting urothelial barrier function improved frequent urination by reducing inflammation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported an association between urothelial barrier dysfunction and inflammation-related LUTD. Spontaneously hypertensive rats (SHRs), which is a rat model of OAB, showed bladder inflammation and impaired urothelial barrier function with a decreased number of UPs [ 18 ]. In the SHRs, supporting urothelial barrier function improved frequent urination by reducing inflammation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneously hypertensive rats (SHRs), which is a rat model of OAB, showed bladder inflammation and impaired urothelial barrier function with a decreased number of UPs [ 18 ]. In the SHRs, supporting urothelial barrier function improved frequent urination by reducing inflammation [ 18 ]. Previous studies showed increased inflammatory cells and decreased UPs in OAB patients compared to healthy individuals [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 132 ] 2. [ 140 ] Hypericum perforatum Hypericaceae St John’s wort Flowering top Inhibited EFS-induced contractility Rat urinary bladder strips The inhibitory effect on excitatory transmission involve opioid receptors, at least partly [ 27 ] Perilla frutescens Lamiaceae Beefsteak plant Leaf Increased in the micturition interval, improved frequent urination Female SHR rats Improvement of the urothelial presence, anti-inflammatory effects [ 84 ] Peucedanum japonicum Apiaceae Coastal hog fennel Whole plant extract / Isosamidin 1. The extract inhibited agonist-induced rabbit bladder contractile response; decreased micturition frequency 2.…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese medicinals, the stems, leaves, and seeds of P. frutescens are commonly used as effective medicines for treating pain, colds, cough, nausea, poisoning, asthma and constipation [ 19 ]. Modern studies have shown that P. frutescens has anti-bacterial [ 20 ], anti-inflammatory [ 21 23 ], anti-cancer [ 24 ], anti-viral [ 25 , 26 ], and anti-aging effects [ 27 ]. Most of these studies have focused on the inhibitory effects of P. frutescens extracts on the common bacteria and plant fungi in daily foods [ 20 , 28 ].…”
Section: Introductionmentioning
confidence: 99%